Dietetic service provision and nutritional interventions provided to patients with head and neck sarcoma: Findings from a national United Kingdom centre five-year audit - Florence Cook; Dimitris Tatsis; Malla Salli; Deepti Sinha; Nicholas Kalavrezos (Oral Oncology Reports)
Objectives: Head and neck sarcomas (HNS) represent a subset of malignancies which may be treated with multiple-modalities including chemotherapy followed by surgery and/or radiotherapy. Malnutrition is common in head and neck cancer (HNC) but limited literature exists determining nutritional interventions required in HNS. This audit aimed to investigate the dietetic input and nutritional interventions in HNS at a London sarcoma centre according to evidence-based HNC nutritional guidelines. Methods: Retrospective review between January 2018 to January 2023. Adult patients (≥18 years) newly-diagnosed with HNS treated at the tertiary centre were included. Demographic data and information on nutritional interventions was collected and statistically analysed. Results: 337 patients were referred to the HNS multidisciplinary meeting; 154 met the inclusion criteria; 66 received dietetic intervention (age = 45 [30.5] years; 47% (n = 31) male; baseline weight = 70.3 ± 18.13 kg; BMI = 24.2 [8.47] kg/m2). 19.7% (n = 13) were malnourished at presentation. Nutritional interventions were as follows: dietary counselling 100% (n = 66); oral nutritional support 90.9% (n = 60); oral nutritional supplements 75.8% (n = 50); enteral tube-feeding 54.5% (n = 36). 15.2% (n = 10) had a prophylactic gastrostomy; n = 4 pre-surgery and n = 6 pre-radiotherapy/proton-beam therapy±chemotherapy with 100% and 33.3% using the tube for ≥4 weeks respectively. Average duration of dietetic intervention was significantly longer for patients with high grade sarcoma compared to low grade (411.5 days and 136.8 days respectively, p = 0.000039) and for those undergoing multi-modality treatment compared to single-modality (402.9 days and 187.7 days respectively, p = 0.000932). Conclusion: A fifth of patients with HNS were malnourished at presentation and the majority receiving dietetic intervention required nutrition support, indicating the need for nutritional management in HNS.